Minority Muslim In Budakeling Village, Bebandem, Karangasem, Bali Living In Harmonious Tolerance - Ainiyah, Qurrotul; Mirrota, Dita Dzata; Anans, Merli Zia (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Budakeling people in Bebandem, Karangasem, Bali, consists of various religions. but they live in harmony and tolerance without conflict, Muslims are a minority in that village. This research aims to describe the harmonious, tolerant life experienced by minority Muslims in the Budakeling Karangasem Bali. This is field research, with a qualitative descriptive approach. The participants were village officials, Javanese saren hamlet traditional keliang, Islamic religious leaders, Muslim and Hindu citizens. Data collection techniques were observation, interviews, and documentation. The results of this research were the life of minority Muslims is fair, getting equal opportunities, both in social life and public services. Harmonization of the lives of minority Muslims can be seen from the burcek, Subak and the use of Hindus’ name prefixes for Muslims, and Typical gamelan rudat.